PAPP-A activity is increased in cerebrospinal fluid from patients with diabetic polyneuropathy and correlates with peripheral nerve impairment. (October 2019) - Kallestrup, M.; Frystyk, J.; Espelund, U.; Hjortebjerg, R.; Tankisi, H.; Andersen, H.
Abstract: Objective: Insulin-like growth factors (IGFs) have neuroprotective effects. IGF activity is partly controlled by pregnancy-associated plasma protein-A (PAPP-A), an enzyme which enhances IGF-action by cleavage of IGF-binding protein-4 (IGFBP-4). To study the role of PAPP-A and the IGF system in diabetic polyneuropathy (DPN), we measured immunoreactive (total) concentrations of IGF-I and IGF-II, bioactive IGF by cell-based bioassay, PAPP-A, as well as intact and PAPP-A-cleaved IGFBP-4 in cerebrospinal fluid (CSF) and serum from patients with type 2 diabetes (T2D) with and without DPN. Design: Twenty-three patients with T2D were included. Based on clinical examination, vibratory perception thresholds and nerve conduction studies, patients were diagnosed with ( n = 9) or without ( n = 14) DPN. Results: In CSF, PAPP-A activity, as estimated by IGFBP-4 fragment levels, was higher in patients with than without DPN (34.57 vs 13.79 μg/L, p = .003) and concentrations correlated with peripheral nerve impairment measures ( r = 0.73, p < .01). Furthermore, serum bioactive IGF was lower in patients with than without DPN (0.8 vs 1.3 μg/L, p = .006) and correlated inversely to the severity of DPN ( r = −0.67, p < .01). Conclusions: In both CSF and serum, members of the IGF system correlated with measures of peripheral nerve impairment in patients with T2D. This supports a relationship between the IGF system and the development of DPN. Further studies are needed to clarify if these changes are causally linked to the pathogenesis of DPN. Highlights: PAPP-A activity is increased in the cerebrospinal fluid in type 2 diabetic patients with polyneuropathy. PAPP-A activity in the cerebrospinal fluid correlates with the severity of diabetic polyneuropathy. Serum bioactive IGF is decreased in participants with type 2 diabetes and polyneuropathy. Serum bioactive IGF correlates inversely with severity of diabetic polyneuropathy. The IGF system may be linked to the development of diabetic polyneuropathy.